Men, caregiving and the media : the dad dilemma - Hunter, Sarah C., 1991-; Riggs, Damien W. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Analysing diverse media representations of men who provide primary care to their children, this book demonstrates how the practice of fatherhood - and of masculinity - is changing, and the ways media representations sensationalise and reinforce gender inequities in regards to carework"--
OCLC-licensed vendor bibliographic record.
Keywords: Fatherhood; Male caregivers; Child care; Masculinity; SOCIAL SCIENCE / Gender Studies